C♯ 7 quick syntax reference : a pocket guide to the language, APIs and library - Olsson, Mikael (Web programmer) (Apress, 2018)
This quick C# 7 guide is a condensed code and syntax reference to the C# programming language, updated with the latest features of C# 7.3 for .NET and Windows 10. It presents the essential C# 7 syntax in a well-organized format that can be used as a handy reference. In the C# 7 Quick Syntax Reference, you will find a concise reference to the C# language syntax: short, simple, and focused code examples; a well laid out table of contents; and a comprehensive index allowing easy review. You won't find any technical jargon, bloated samples, drawn-out history lessons, or witty stories. What you will find is a language reference that is concise, to the point, and highly accessible. The book is packed with useful information and is a must-have for any C# programmer. You will: Discover what's new in C# 7.3 and .NET for Windows 10 programming, including out values, ref locals and returns, local functions, throw exceptions, and numeric literals Create lightweight, unnamed types that contain multiple public fields Create branching logic based on arbitrary types and values of the members of those types Nest functions inside other functions to limit their scope and visibility Throw expressions in code constructs that previously were not allowed Declare methods with the async modifier to return other types in addition to Task Use the new numeric literals found in C# 7.3 to improve readability for numeric constants.